DEVELOPMENT OF AN EXPERIMENTAL STAND FOR RESOURCE RESEARCH OF A FLOW DIVIDER WITH COMPENSATION RODS - RUTKEVYCH, VOLODYMYR; SHARGORODSKIY, SERHIY; OSTAPENKO, ALEXEI (Herald of Khmelnytskyi National University. Technical sciences, 2025)
A comprehensive analysis of the operating conditions of modern hydraulic drives was carried out, their advantages, disadvantages and current areas of improvement were identified. Particular attention was paid to the issues of increasing the reliability, durability and adaptability of the hydraulic drive to changes in technological loads on the working bodies of agricultural machines. The design of an experimental stand was proposed, intended for resource tests of a throttling flow divider with a compensation rod, developed for a cut-out mechanism for unloading silage from trench storages. Previous studies revealed some design flaws in the throttling flow divider when operating for about 2·10⁴ cycles. Based on the analysis of operating conditions, changes were made to the design of the hydraulic drive element, after which repeated tests showed a significant increase in its reliability and stability of operation - the operating life exceeded 6.6·10⁵ load cycles. The basis of hydraulic drives is hydraulic devices of the spool and throttle type, they remain the main components of a modern hydraulic drive, capable of increasing the energy, dynamic, cost characteristics and increasing the reliability and durability of this drive. The results of the research confirmed the feasibility of using the developed throttle flow divider with a compensation rod as part of the hydraulic systems of cutting mechanisms, which ensures an increase in their operational durability and a reduction in the risk of failures during operation. Promising directions for further research were identified, which consist in the comprehensive optimization of design parameters, the implementation of adaptive control systems and the study of the influence of real load modes on the resource of hydraulic elements.
Keywords: cutting mechanism; silo; hydraulic drive; pump; throttle flow divider; distributor; reliability; experimental stand; resource; operating life